Margin call [videorecording (DVD)] - Chandor, J. C.; Chandor, J. C.; Spacey, Kevin; Bettany, Paul, 1971-; Irons, Jeremy, 1948-; Quinto, Zachary; Quinto, Zachary; Moore, Demi; Tucci, Stanley (Lions Gate Films, Inc, 2011)
Who cares about the suffering--existential, financial, or other--of those who blindly mismanaged our monies into this ever-expanding, nay, verily bottomless pit of debt? No one, but this film may help viewers understand A) the birth of current financial woes, and B) what it might have been like, in those first few hours within the confines of an early investment trading firm casualty. Fueled by a mass layoff, a thumb drive, and a rocket-scientist-cum-analyst who really understands the numbers, the last night of good times on Wall Street unfolds as rung by rung, up the executive ladder, travels news that is -- apocalyptic. For viewers who still have no idea of how 2008's meltdown happened, this film is one fiction that will make it ever so much more real.